1993
DOI: 10.3928/0098-9134-19930401-06
|View full text |Cite
|
Sign up to set email alerts
|

CERUMEN IMPACTION Prevalence and Detection in Nursing Homes

Abstract: 1. Many people, including health care professionals, believe that hearing loss is a normal part of aging and that little can be done to improve older adults' hearing. If the staff and physicians believe that hearing loss among nursing home residents is expected due to advanced age, then the likelihood of further evaluation of hearing impairments is minimal. 2. Hearing loss is a serious health problem among the elderly. Social isolation, depression, acting out inappropriately, and paranoia have been related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…One study found a rate of 25% of cerumen impaction (at least 1 canal totally occluded) among residents of 8 nursing homes. 23 …”
Section: Planning Care For Residents With Hearing Lossmentioning
confidence: 99%
“…One study found a rate of 25% of cerumen impaction (at least 1 canal totally occluded) among residents of 8 nursing homes. 23 …”
Section: Planning Care For Residents With Hearing Lossmentioning
confidence: 99%
“…When coupled with an increase in the number and coarseness of cilia in the ear canal, especially in males, the result is a linear increase in the percentage of elderly patients with excessive cerumen (Ruby, 1986;Gleitman et al, 1992). Of note is the work of Mahoney (1987Mahoney ( , 1993, who carried out longitudinal studies on the prevalence of excessive cerumen in nursing home residents and found 34-57% with "moderate to large" amounts of cerumen.…”
mentioning
confidence: 98%
“…Estimates suggest that between 19% and 65% of patients >65 years old have cerumen impaction 13,15 and that elderly patients in nursing homes are likely at the upper end of this spectrum. 10,18 In the developmentally delayed adult population, 28% to 36% have excessive or impacted cerumen. 10,11 Moreover, the presence of cerumen impaction has been associated with hearing loss 19 and diminished cognitive function 15 in these populations.…”
Section: Health Care Burdenmentioning
confidence: 99%